Fiberoptic Endoscopic Examination of Swallowing (FEES) Evaluation in Post Stroke Patients - Puspa Zuleika; Abla Ghanie; Adelien; Indriati Purwasari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2020)
Introduction. Complications caused by post-stroke dysphagia increase the morbidity and mortality of patients. Although it has a significant effect on the functional abilities and worsening of the patient's prognosis, post-stroke dysphagia is still under-noticed and often undiagnosed. The importance of knowing the incidence of post-stroke dysphagia, not only to determine its relationship to the pathology of the disease but also to determine treatment plans or follow-up interventions. This study aims to determine the incidence of FEES findings in post-stroke dysphagia both hemorrhagic and non-hemorrhagic stroke. Methods. Forty post-stroke patients in the Inpatient and Outpatient Installation of the THTKL Section and the Neurology Section of Dr. Hospital. Mohammad Hoesin Palembang conducted a FEES examination to see leakage, residue, penetration, and aspiration after being given six different types of food boluses ranging from filter porridge, rice porridge, oatmeal, water, milk, and biscuits. The results of the assessment are recorded and analyzed descriptively. Results. From 40 research subjects found 25 people experiencing dysphagia, where subjects with non-hemorrhagic stroke types were 21 people (52.5%), while hemorrhagic stroke types were four people (10%). The occurrence of leakage of filter porridge was 5 findings, leakage of rice porridge was eight findings, oatmeal leakage, water, and milk were seven findings each, and biscuit leakage was two findings. The incidence of filtered pulp residues was 12 findings, rice porridge residues were 14 findings, oatmeal residues were 15 findings, water and milk residues were five findings each, and biscuit residues were eight findings. The incidence of penetration of filter porridge, rice porridge, and biscuits was one finding each, oatmeal penetration was not found, while water and milk penetration were six events each. The aspirations of filter porridge, rice porridge, oatmeal, and biscuits were not found, while water and milk aspirations were seven findings. Conclusion. The incidence of dysphagia in post-stroke patients both hemorrhagic and non-hemorrhagic in the Inpatient and Outpatient Installation of the THTKL Section and the Neurology Section of the Mohammad Hoesin Hospital Palembang Palembang is quite high at 62.5%. The occurrence of food residues is the most FEES findings. While aspirations are the fewest findings.